2018
DOI: 10.5694/mja17.00725
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in the incidence of invasive melanoma in Victoria, 1985–2015

Abstract: Melanoma remains a significant health problem, warranting continued prevention efforts. Awareness of differences in presentation by men and women and in different age groups would facilitate improved screening and risk identification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 25 publications
2
16
0
Order By: Relevance
“…There may have been selection bias as the VMS is a statewide tertiary referral service to which patients with advanced or aggressive disease are more likely to have been referred. Nevertheless, overall findings on melanoma distribution were consistent with statewide cancer registry data, despite invasive melanoma being overrepresented (76.6% in our cohort vs 56.1% Victorian Cancer Registry) . Furthermore, like other population studies, we found consistency in melanoma incidence rates between contiguous sites with similar sun exposure (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…There may have been selection bias as the VMS is a statewide tertiary referral service to which patients with advanced or aggressive disease are more likely to have been referred. Nevertheless, overall findings on melanoma distribution were consistent with statewide cancer registry data, despite invasive melanoma being overrepresented (76.6% in our cohort vs 56.1% Victorian Cancer Registry) . Furthermore, like other population studies, we found consistency in melanoma incidence rates between contiguous sites with similar sun exposure (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…1 Although there is a lower incidence of MCC than melanoma (46.0 per 100 000 population age-standardised in Victoria 2015), there are similar trends in increase in the older population with higher rates among men. 16 As with other skin cancers the link between UV radiation in the development of MCC is well noted. 2 The rates on MCC were correlated with melanoma regardless of geographical latitude.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of invasive melanoma in Australia continues to rise in older age groups, but it has plateaued and decreased in younger age groups over recent years 6,7 . In contrast, over a 20‐year period, incidence of in situ melanoma has increased in all age groups 3 .…”
Section: Current Australian Screening Policy and Practicementioning
confidence: 99%
“…5 The incidence of invasive melanoma in Australia continues to rise in older age groups, but it has plateaued and decreased in younger age groups over recent years. 6,7 In contrast, over a 20-year period, incidence of in situ melanoma has increased in all age groups. 3 Based on Medicare data, skin biopsy rates have also increased by 66% over the past decade 8 and the economic burden is increasing steadily.…”
mentioning
confidence: 99%